The human person as centre of every health care system. - Bignamini, Angelo A. (Medicina e Morale, 2002)
Healthcare organisation is the set of structures, functions and responsibilities that should guarantee the adequate management of health care in a defined environment. The subjects involved in the healthcare system are the attending (healthy and sick) persons, the professionals (physicians and non medical healthcare operators), the environment in which it is realised (the society). It is therefore the crossing point of three specifically human entities: medicine, ethics, and society. The requirements for an adequate healthcare organisation imply therefore that the basic principle of medicine, ethics, and society co-exist. Medicine puts at its centre the need of the human being who encounters the limit to its native right to life (that is, death) and to health preservation (that is, illness). Society requires to find a balance between the response capacity of community in its entirety, including the spontaneous capacity of aggregation and service, according to priorities determined by the nature of the subject of the need (the sick human being) and not prejudicially defined by an observer. Ethics safeguards the native subject's rights, determining procedures consistent with the nature of everyone implied into the design and management of the healthcare organisation. In an ontologically based bioethic approach, the main criteria are those related to the autonomously existent subjects, thus to the human being. In suborder and on a dialogic relationship with them, the second criteria are, that is, those related to entities per se not existing unless the autonomous subjects exist: society and, in further subordination, the "government", regional, national, or federal. Alternative views exist, in which the main criteria are instead those, of Enlightenment derivation, relevant to the "collectivity", to the "state", to which the "individual" should be subordinate. Already the use of "individual" opposed to "person" focuses on how this approach is ideological (based on abstract hypotheses defined a priori) rather than scientific (based on the observation of reality). The two approaches originate healthcare organisations and systems opposed to each other, with different roles also for the operators and, mainly, for the physician. In the Enlightenment model of "ethical state", the mathematical-statistical and mathematical-economic instruments (DRG, EBM, guidelines) become interpretative cages (ideology) of reality. In the social model all available instruments are employed as one of the possible means, along with science, conscience and compassion, to describe the complex reality of the individual person who seeks a relationship with the physician, bringing along his or her own needs, expressed or unexpressed, in relation to the health status. According to the person centered bioethics, the criterion that justifies whichever system and whichever organisation, including the organisation of the healthcare system, is the "good" of all subjects (sick persons and professionals with equal dignity). This becomes manifest in the protection of their rights, first of all the right to the preservation of life and integrity, to the safeguard of health, to the respect of moral and religious criteria of each one. Within this context the person remains the central reference of the "organisation"; the respect of the nature of the human being remains the measure of its validity; the possibility of the "good" of the person remains the yardstick of its value. Experiences currently being carried out according to this vision, incidentally, appear not to be less efficient than those based on the opposite view. In this context the physician, being the operator nearest to the subject, assumes also the responsibility to act as the advocate of the rights of the sick person (ethical function) in front of the system, rather than being just a "service supplier", since healthcare can not be reduced to a "product" or "service", nor can be compressed into the definition of "client" or "user" the sick person.